Citra Perempuan Kolonial dalam Kehidupan Beragama di Sumatera Timur, 1870-1942 - Suriani Suriani; Tiara Desthy Afrina; Wilda Febriani (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
The opening of tobacco plantations in East Coast Sumatra in 1870 became a major factor in the creation of ethnic, cultural, and religious diversity in there. All the Malays there were Muslim, then the Europeans came with their Christianity, which was followed by most of the Batak people, the Indians brought Hinduism and Sikhism, and the Chinese brought Buddhism. East Coast Sumatra is a pluralistic region, but there has never been a conflict between ethnicities or religions. Very interesting. However, the reality of the religious life of the people at that time had never been revealed in detail. Furthermore, during the 1930 census it was recorded that there were 4.293 Europeans in Medan and 2.001 of them were women, but their presence in the religious sphere has not been exposed. Therefore, this study aims to narrate the image of colonial women in religion in East Coast Sumatra. The images of colonial women in this study are all forms of mental, spiritual, and daily behaviour expressed by women in religion, including the outward appearance that appears in women and their religious activities in East Coast Sumatra in the period 1870-1942. This study uses the historical method, and the primary data are the Dutch Colonial Government Report (verslag),Volkstelling 1930, maps, newspapers, bulletins and magazines, photographs depicting the religious life of the people of East Sumatra in the period 1870-1942.